MODEL ANALISIS JALUR TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MATEMATIKA - Desi Rahmawati; Taba Heri Setiawan (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Learning, namely the activity of someone who doesn't know to know, whether someone is successful or not in learning can be seen from the learning outcomes or we know it as an evaluation during the learning process. The results of self-study at school are called report cards. There are several factors that can affect student learning outcomes, namely student learning styles, interest in learning and learning motivation. The purpose of this study is to determine the form of the path equation that describes the relationship between variables and to determine the effect between variables. This study took a sample at SMAN 8 Kab. Tangerang grades 11 & 12, majoring in MIA, totaling 125 students from an affordable population of 180 students, taking the form of questionnaires and interviews, the variables used in this study are learning style (X1), interest in learning (X2), learning motivation (Y) and learning outcomes (Z), tests carried out before path analysis, namely validity test, reliability test, normality test, multicollinearity test, linearity test. Based on the research results, the form of the path equation that describes the relationship between learning styles, interest in learning, and learning motivation towards mathematics learning outcomes The results of the analysis equation 1= 0,277 + 0,601 + 0,799 1 Results of the analysis equation 2    + y1 = -0,216+ 0,445  + (-0,069) + 0,985 1 The influence of learning styles, interest in learning and learning motivation on mathematics learning outcomes: 1) There is a positive and significant relationship between learning style variables (X1) and learning motivation (Y), 2) There is a positive and significant relationship between learning interest variables (X2) with learning motivation (Y), 3) There is no positive and significant relationship between learning style variables (X1) and learning outcomes (Z), 4) There is a positive and significant relationship between learning interest variables (X2) and learning outcomes (Z), 5) There is no positive and significant relationship between learning motivation variables (Y) and learning outcomes (Z), 6) There is no positive and significant relationship between learning style variables (X1) and learning outcomes (Z) through learning motivation (Y), 7) There is no positive and significant relationship between the learning interest variable (X2) and learning outcomes (Z) through learning motivation (Y).